Advertisement and release calls of Phyllomedusa ayeaye (Anura: Hylidae) with comments on the social context of emission - Nali,Renato C. (2015)
ABSTRACT Male calls play different roles in anuran social organization, such as spacing, territoriality and female attraction. However, calls and associated behaviors remain poorly described for many anuran species. Here we describe the advertisement and release calls of the tree frog Phyllomedusa ayeaye (Lutz, 1966) and report on the social context of emissions and a physical combat. Approximately 35 minutes of digital recordings were obtained from 34 hours of observations at one breeding site in the state of Minas Gerais, southeastern Brazil. Bioacoustic analysis showed that males emitted two types of advertisement calls: 1) simple call (a sequence of short pulsed notes) and 2) composite call (a sequence of short pulsed notes followed by a long pulsed note). Composite calls were emitted more frequently during more intense chorus activity, with various active males at the breeding site. The release call was also composed by short pulsed notes, with a wider spectrum of frequencies and emitted more rapidly than the advertisement calls. Our results suggest that the composite call of P. ayeaye may represent a mixed advertisement call. Long notes might be the aggressive part directed to males, whereas short notes directed to females. Our description of call types, their functions, and male physical interactions will be useful for studies investigating the systematics and behavior of Phyllomedusa species.